2023
DOI: 10.1002/ldr.4731
|View full text |Cite
|
Sign up to set email alerts
|

The contribution rate of stem‐leaf and root of alfalfa (Medicago sativa L.) to sediment and runoff reduction

Abstract: Seasonal changes in ground canopy and root density induced by the growth of alfalfa (Medicago sativa L.) may strongly influence the variation in runoff and sediment across alfalfa growth stages. In this study, eight alfalfa plots with and without ground canopy and two bare soil plots (CK) were used to investigate the effect of alfalfa growth on the regulation of runoff and sediment during one growing season (seedling stage, S1; budding stage, S2; flowering stage, S3; podding stage, S4). The experiments involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(155 reference statements)
0
0
0
Order By: Relevance
“…The PCA results showed that lower soil compaction leads to postponed pond forming on the soil surface layer and the start of the Runoff, which was also observed previously [94][95][96][97]. Moreover, the WSA showed a positive relation with TP and TR because of (1) WSA's capability to create channels within the soil that will enable water to infiltrate and move down the soil profile, which will improve the soil's ability to store more water, thus reducing the water available for runoff [98,99], (2) higher aggregate stability will prevent crusting, since the soil particles are bounded into aggregates that are less prone to soil detachment during the raindrop impact [97,100], and (3) well-aggregated soil had a rougher surface texture due to the presence of clumps and particles, which will enlarge the surface area for rainfall catchment [101].…”
Section: Interrelations Between Propertiessupporting
confidence: 84%
“…The PCA results showed that lower soil compaction leads to postponed pond forming on the soil surface layer and the start of the Runoff, which was also observed previously [94][95][96][97]. Moreover, the WSA showed a positive relation with TP and TR because of (1) WSA's capability to create channels within the soil that will enable water to infiltrate and move down the soil profile, which will improve the soil's ability to store more water, thus reducing the water available for runoff [98,99], (2) higher aggregate stability will prevent crusting, since the soil particles are bounded into aggregates that are less prone to soil detachment during the raindrop impact [97,100], and (3) well-aggregated soil had a rougher surface texture due to the presence of clumps and particles, which will enlarge the surface area for rainfall catchment [101].…”
Section: Interrelations Between Propertiessupporting
confidence: 84%